Structural Components of Indigenous Diabetes Care: An Indigenous-informed Scoping Review - Brendon McIntosh; Lisa Kremer; Anneka Anderson; Joanna Hikaka (Journal of Racial and Ethnic Health Disparities, 2026)
Abstract Background Māori in Aotearoa New Zealand (Aotearoa NZ), Aboriginal and Torres Strait Islander peoples in Australia, First Nations, Inuit and Métis peoples in Canada, and American Indian and Alaska Native peoples in the United States experience substantial inequities in type 2 diabetes. While numerous diabetes programs for Indigenous populations have been described across these countries, the structural features that characterise Indigenous models of diabetes care remain less clearly articulated. This scoping review aimed to identify and describe the structural components of Indigenous models of diabetes care reported in literature from Aotearoa NZ, Australia, Canada and the United States. Methods A scoping review was conducted following the Arksey and O’Malley framework, with methodological guidance from the Joanna Briggs Institute and Indigenous-informed scoping review approaches. Electronic databases and grey literature sources were searched to identify studies describing Indigenous diabetes initiatives in Aotearoa NZ, Australia, Canada and the United States. Database searches identified 10,683 records. Following the removal of 10 retracted publications and 4,642 duplicate records, 6,031 records underwent title and abstract screening. Full-text articles were assessed against the eligibility criteria, resulting in 38 included studies. Data were charted using a structured extraction template capturing program characteristics, governance structures, workforce roles, delivery settings, and care practices. Extracted data were analysed to identify recurring structural components of Indigenous diabetes initiatives. Component domains were refined through iterative discussions with the research team and a kaumātua (esteemed elder) advisory rōpū (group) . Frequency counts were generated to map the presence of components across the included studies. Results Thirty-eight sources were included in the review. Ten components of Indigenous diabetes care were identified and grouped into three domains: governance and service design, workforce and delivery structures, and cultural foundations of care. The most frequently reported components included cultural–clinical integration, Indigenous workforce roles, culturally safe care structures and accountability, and Indigenous governance and leadership. Programs were commonly delivered in community settings and often used hybrid workforce models that combined clinical professionals with Indigenous health workers, navigators, or peer educators. Many initiatives also embedded cultural practices and Indigenous knowledge systems within program delivery. Conclusion Indigenous diabetes initiatives across Aotearoa NZ, Australia, Canada and the United States are characterised by integrated models of care that combine governance structures, culturally grounded workforce roles, community-based delivery environments, and cultural foundations of care. By synthesising these structural components, this review provides a framework for understanding how Indigenous diabetes initiatives are organised and delivered. The findings may inform future research, service design, and policy development to improve diabetes care for Indigenous communities. Registration A formal protocol was developed prior to commencing screening and extraction; however, it was not prospectively registered.